2019
DOI: 10.15252/embj.2018100554
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic lipid binding activity of ATG 16L1 supports efficient membrane anchoring and autophagy

Abstract: Membrane targeting of autophagy‐related complexes is an important step that regulates their activities and prevents their aberrant engagement on non‐autophagic membranes. ATG16L1 is a core autophagy protein implicated at distinct phases of autophagosome biogenesis. In this study, we dissected the recruitment of ATG16L1 to the pre‐autophagosomal structure (PAS) and showed that it requires sequences within its coiled‐coil domain (CCD) dispensable for homodimerisation. Structural and mutational analyses identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 47 publications
4
63
0
Order By: Relevance
“…Interestingly, silencing of ATG16L1 did not only affect downstream LC3B puncta, but also reduced WIPI2 structures. This was surprising, since depletion of WIPI1 or WIPI2 was previously shown to strongly reduce recruitment of ATG16L1, suggesting WIPI1/2 to be upstream of ATG16L1 (Bakula et al, 2017;Dooley et al, 2014;Dudley et al, 2019). Our result suggests a positive feedback of ATG16L1 recruitment on WIPI2 stability on membranes, similar to the finding that PI3P stabilizes the upstream ULK complex on phagophores by directly interacting with ATG13 (Karanasios et al, 2013).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Interestingly, silencing of ATG16L1 did not only affect downstream LC3B puncta, but also reduced WIPI2 structures. This was surprising, since depletion of WIPI1 or WIPI2 was previously shown to strongly reduce recruitment of ATG16L1, suggesting WIPI1/2 to be upstream of ATG16L1 (Bakula et al, 2017;Dooley et al, 2014;Dudley et al, 2019). Our result suggests a positive feedback of ATG16L1 recruitment on WIPI2 stability on membranes, similar to the finding that PI3P stabilizes the upstream ULK complex on phagophores by directly interacting with ATG13 (Karanasios et al, 2013).…”
Section: Discussionsupporting
confidence: 80%
“…ATG16L1 emerges as an important hub for specific cargo to connect to the autophagy machinery. It forms a complex with ATG5 and ATG12 for LC3 lipidation and has binding sites for FIP200 and WIPI2 (Dooley et al, 2014;Gammoh et al, 2013), for phosphoinositides (Dudley et al, 2019) and generally for membranes (Lystad et al, 2019). On the other hand, it was shown to interact with TRIM16, an E3 ubiquitin ligase required for autophagy of damaged lysosomes by connecting to galectin3 on exposed glycans (Chauhan et al, 2016), and with TMEM59 involved in autophagic degradation of late endosomes/lysosomes and Staphylococcus aureus-containing phagosomes (Boada-Romero et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…5c). Finally, in conditions of PI3KC2α depletion, we analyzed the behavior of ATG16L1, a crucial regulator of early autophagic processes, notably as a key partner of WIPI2 and PI3P in autophagy regulation 29,30 , and known to be recruited to the basal body in PC associated autophagy 31 during shear stress 18 . Importantly we showed that, as observed for Rab11a and WIPI2, ATG16L1 was mobilized by shear stress but not in siPI3KC2α transfected cells ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…LC3-II conversion was more than 50% complete with DO lipids after 30 min, while a comparable degree of conversion required overnight incubation with PO lipids. This effect cannot be explained by preferential membrane binding by the E3 complex (Dudley et al, 2019;Lystad et al, 2019), as PO and DO lipids are bound equally (Figure S1G, H). These data, which are consistent with a high proportion of unsaturated lipids in autophagosomal membranes (Schütter et al, 2020), suggest that the presence of two rather than one unsaturated tail in the lipids of the membrane substrates increases the flexibility of the membrane, facilitating structural rearrangements necessary for LC3 lipidation.…”
Section: Reconstitution Of Pi(3)p-and Wipi-dependent Lc3 Lipidationmentioning
confidence: 94%